Single-Cell RNA Sequencing of Retina:New Looks for Gene Marker and Old Diseases - Ying, Peixi; Huang, Chang; Wang, Yan; Guo, Xi; Cao, Yuchen; Zhang, Yuxi; Fu, Sheng; Chen, Lin; Yi, Guoguo; Fu, Min (Frontiers in Molecular Biosciences, 2021)
The retina is composed of 11 types of cells, including neurons, glial cells and vascular bed cells. It contains five types of neurons, each with specific physiological, morphological, and molecular definitions. Currently, single-cell RNA sequencing (sRNA-seq) is emerging as one of the most powerful tools to reveal the complexity of the retina. The continuous discovery of retina-related gene targets plays an important role in helping us understand the nature of diseases. The revelation of new cell subpopulations can focus the occurrence and development of diseases on specific biological activities of specific cells. In addition, sRNA-seq performs high-throughput sequencing analysis of epigenetics, transcriptome and genome at the single-cell level, with the advantages of high-throughput and high-resolution. In this paper, we systematically review the development history of sRNA-seq technology, and summarize the new subtypes of retinal cells and some specific gene markers discovered by this technology. The progress in the diagnosis of retinal related diseases is also discussed.